NOVEL APPROACHES IN OBESITY TREATMENT: THE PROMISE OF GENE THERAPIES - Karolina Błądzińska; Anna Opalińska; Cezary Lubas; Paula Folta; Kacper Szeląg; Joanna Kłosowska; Maciej Błądziński; Małgorzata Zach; Piotr Świerczek; Antoni Kujawski (International Journal of Innovative Technologies in Social Science, 2025)
Introduction and Purpose: Obesity constitutes a significant global public health concern driven by multifactorial interactions among genetic, metabolic, and environmental determinants [2, 7, 13, 28]. Conventional interventions—including lifestyle modification, pharmacotherapy, and bariatric procedures—frequently provide only limited or temporary benefits [2, 21]. This review evaluates emerging gene-based therapeutic strategies designed to target the molecular pathways responsible for obesity development and progression. Current State of Knowledge: Preclinical animal studies utilizing adeno-associated virus (AAV) vectors have demonstrated effective adipose-tissue-specific gene delivery, resulting in enhanced thermogenesis, improved insulin sensitivity, and measurable reductions in adiposity [8, 10, 12, 16, 26]. Key metabolic regulators, such as fibroblast growth factor 21 (FGF21), uncoupling protein 1 (UCP1), and elements of the leptin–melanocortin axis, have shown promising modulation in experimental models [4, 8, 9, 22,32]. Furthermore, adipose-derived mesenchymal stem cells are being explored as potential vehicles for targeted gene delivery, although these approaches remain in early developmental phases [14]. Clinically, the most advanced gene-based interventions include RNA interference (RNAi) platforms—particularly modulators of pathways such as ALK7 or INHBE—which are currently undergoing evaluation for obesity management [ 23, 31]. Summary: While gene therapy applications for obesity remain primarily experimental, emerging evidence underscores their potential to address fundamental metabolic dysfunction rather than merely mitigate clinical manifestations [8, 18, 24]. Advancements in vector precision, tissue-targeted delivery, and long-term safety evaluation will be essential for future translation into clinical practice [10, 11, 26]